2014
DOI: 10.1155/2014/532161
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Induced Doxorubicin Resistance in Triple Negative Breast Cancer

Abstract: Triple negative breast cancer (TNBC) is an aggressive histological subtype with limited treatment options and a worse clinical outcome compared with other breast cancer subtypes. Doxorubicin is considered to be one of the most effective agents in the treatment of TNBC. Unfortunately, resistance to this agent is common. In some drug-resistant cells, drug efflux is mediated by adenosine triphosphate-dependent membrane transporter termed adenosine triphosphate-binding cassette (ABC) transporter, which can drive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 57 publications
1
56
0
Order By: Relevance
“…The tumor microenvironment can also stimulate the development of drug resistance by changing the gene transcription within cancer cells to override the cytotoxicity or increase efflux of anticancer drugs [ 53 ]. Numerous in vitro and in vivo studies reported that cytokines are capable of modulating the expression and function of different drug transporters including P-gp, MRPs, and ABCG2 [ 22 , 54 ]. In our previous study [ 22 ], we also found that a cell line established from adipose-derived mesenchymal stem cell (MSC-ad) secretes IL-8 and gives rise to resistance against chemotherapy in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor microenvironment can also stimulate the development of drug resistance by changing the gene transcription within cancer cells to override the cytotoxicity or increase efflux of anticancer drugs [ 53 ]. Numerous in vitro and in vivo studies reported that cytokines are capable of modulating the expression and function of different drug transporters including P-gp, MRPs, and ABCG2 [ 22 , 54 ]. In our previous study [ 22 ], we also found that a cell line established from adipose-derived mesenchymal stem cell (MSC-ad) secretes IL-8 and gives rise to resistance against chemotherapy in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cells are maintained in 10-cm dishes in Leibovitz’s L-15 medium (Thermo Fisher Scientific, Waltham, MA, USA). All cells were supplemented with 10% fetal bovine serum (FBS; Thermo Fisher Scientific, Waltham, MA, USA), penicillin (100 U/mL) and streptomycin (100 μg/ml) cocktail (Thermo Fisher Scientific, Waltham, MA, USA), and were maintained in a 37 °C incubator without CO 2 supply [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our co-culture, stromal cells from liver and adipose also supported the proliferation of K562 cells. Recent reports have demonstrated that adipose tissue and associated stroma can maintain breast cancer cells and induce pharmacological resistance [34,35]. Additionally, the links between adipose tissue and activation of inflammation and chemokine pathways with regard to oncogenesis is becoming more recognized [36].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that BMMSC play important roles in tumor progression and promote invasion and metastasis in various cancers . In the tumor microenvironment, upon interaction with MSC, breast cancer cells showed altered biological functions of certain gene clusters, hence increasing stemness of tumor cells, migration ability, angiogenesis, and drug resistance . Li et al showed that MSC were mainly distributed in the tumor stroma after i.v.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In the tumor microenvironment, upon interaction with MSC, breast cancer cells showed altered biological functions of certain gene clusters, hence increasing stemness of tumor cells, migration ability, angiogenesis, and drug resistance. 15 Li et al 16 showed that MSC were mainly distributed in the tumor stroma after i.v. injection and a low frequency MSC were found to be merged into hepatocellular carcinoma tissue.…”
mentioning
confidence: 99%